MOBILITAS PENDUDUK NONPERMANEN DAN KONTRIBUSI REMITAN TERHADAP KEHIDUPAN EKONOMI DAN SOSIAL RUMAH TANGGA DI DAERAH ASAL - Sudibia, I Ketut (PIRAMIDA; Vol 3, No.1 Juli 2007, 2012)
The main objective of this study are to know the remittance contribution from nonpermanent migrants to the economic and social life of their household in the place of origin. It is related to the very important characteristic of nonpermanent migrants, that they still have family such as children, wife, parent, and others in the place of origin who depend on them. On the other hand, the nonpermanent migrants have moral obligation to support the economic and social life of their families. The nonpermanent migrants want to maintain the closely kinship ties between them and their families in home village. Some important findings of this study are: Firstly, the remittance contribution from nonpermanent migrants can increase the household income in the place of origin, and its has improved the household income distribution in the same village. Secondly, the remittance contribution from nonpermanent migrants to the place of origin is not only to fulfill the economic needs but also to support the social needs. Their household in the village origin use remittance for the expenditure of social needs such as ceremonial cost of adat and religion ritual.
Keywords: remittance contribution, nonpermanent migrant, economic needs, and social needs